Microbial Diversity in Landfills through Metagenomics Profiling: A Review - Farah Aisha Mohd Haniff; Hasdianty Abdullah; Mohd Fadzli Ahmad; Maegala Nallapan Maniyam; Hazeeq Hazwan Azman; Nazahiyah Sulaiman; Nor Suhaila Yaacob (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 2 Page (162-171)